Climate variability and dengue cases in cities in the state of Paraíba, Brazil (Research, Society and Development, 2022)
The present study aimed to correlate meteorological variables (rainfall and average air temperature) to reported cases of dengue in cities in the state of Paraíba, from 2007 to 2017. The state of Paraíba presents climate variability due to physical and Atmospheric conditions and variations in these variables generate conditions that favor the increase of breeding sites, consequently the development of the Aedes Aegypti vector and the emergence of diseases transmitted by this mosquito, such as dengue. For this purpose, epidemiological data obtained from the Notifiable Diseases Information System (SINAN) and meteorological data from the Executive Agency for Water Management of the State of Paraíba (AESA) and the National Institute of Meteorology (INMET) were used. Subsequently, these data were spatialized in the Quantum GIS software version 2.14, using the IDW interpolation method. The results showed a low correlation between the two meteorological variables and the reported cases of dengue in the mesoregions of the state. There was a low correlation between air temperature and reported cases of dengue in all mesoregions of the state throughout the study period, and a moderate correlation between reported cases of dengue and rainfall in half of the period. The Borborema and Sertão mesoregions stand out for presenting epidemics in seven of the eleven analyzed years. This condition can be justified by the water crisis due to climate variability, however, it is necessary to analyze other aspects related to the proliferation of the vector, such as socioeconomic issues, with few studies focused on the theme for these mesoregions.